2009
DOI: 10.1016/j.neuroscience.2009.03.080
|View full text |Cite
|
Sign up to set email alerts
|

The genetics of bipolar disorder

Abstract: Bipolar disorder is a mood disorder characterized by impairing episodes of mania and depression. Twin studies have established that bipolar disorder is among the most heritable of medical disorders and efforts to identify specific susceptibility genes have intensified over the past two decades. The search for genes influencing bipolar disorder has been complicated by a paucity of animal models, limited understanding of pathogenesis, and the genetic and phenotypic complexity of the syndrome. Linkage studies hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
188
1
9

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 332 publications
(202 citation statements)
references
References 134 publications
1
188
1
9
Order By: Relevance
“…Intriguingly, a SERT knockout mouse showed reduced brain 5-HT (Bengel et al 1998). Furthermore, an allele of reduced SERT expression is found in patients suffering bipolar disorder and autism (Bartlett et al 2005;Brune et al 2006;Barnett and Smoller 2009). In this study, we identified two distinctive populations of serotonergic neurons in C. elegans: the NSM, ADF, and HSN neurons producing 5-HT and the RIH and AIM neurons absorbing 5-HT from extracellular space but unable to synthesize it.…”
Section: Discussionmentioning
confidence: 81%
“…Intriguingly, a SERT knockout mouse showed reduced brain 5-HT (Bengel et al 1998). Furthermore, an allele of reduced SERT expression is found in patients suffering bipolar disorder and autism (Bartlett et al 2005;Brune et al 2006;Barnett and Smoller 2009). In this study, we identified two distinctive populations of serotonergic neurons in C. elegans: the NSM, ADF, and HSN neurons producing 5-HT and the RIH and AIM neurons absorbing 5-HT from extracellular space but unable to synthesize it.…”
Section: Discussionmentioning
confidence: 81%
“…Indeed, genome‐wide association studies (GWAS) have shown that these disorders are highly polygenic (Barnett & Smoller, 2009; Schizophrenia Working Group of the Psychiatric Genomics, 2014; Shyn et al., 2011) with many genes exerting their influence on numerous neural pathways involved in complex aspects of brain function and likely being impacted upon by environmental events. It has been proposed that individual vulnerability and sensitization to the later development of mental health disorders may partly be regulated through variation in genes encoding proteins that impact on neurotransmitter and hormone systems such as those involved in dopamine, serotonin, and cortisol function (Caspi & Moffitt, 2006; Collip, Myin‐Germeys, & Van Os, 2008; van Winkel, Stefanis, & Myin‐Germeys, 2008; van Winkel, van Nierop, Myin‐Germeys, & van Os, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Even though there is no conclusion about genes directly related to the onset and development of the disorder, a group of genes is altered in its expression patterns contributing to some of the phenotypes found in the brain of BD patients. These include serotonin transporter protein (5-HTT), catechol-O-methyltransferase (COMT), D-amino acid oxidase activator (DAOA), brain-derived growth factor (BDNF), among others (McGowan and Kato, 2008;Barnett and Smoller, 2009;Strakowski, 2012). The presence of polymorphisms of those genes has been suggested as the cause for development of BD (Collier et al, 1996;Sklar et al, 2002;Williams et al, 2006).…”
Section: Pathogenesis Of Bipolar Disordermentioning
confidence: 99%